Stability recovery performance in adults over a wide age range: A multicentre reliability analysis using different lean-and-release test protocols. (26th August 2021) - Werth, J.; Bohm, S.; Klenk, J.; König, M.; Sczuka, K.S.; Schroll, A.; Epro, G.; Mandla-Liebsch, M.; Rapp, K.; Potthast, W.; Arampatzis, A.; Karamanidis, K.
Abstract: The ability to effectively increase the base of support is crucial to prevent from falling due to stability disturbances and has been commonly assessed using the forward-directed lean-and-release test. With this multicentre study we examined whether the assessment of stability recovery performance using two different forward lean-and-release test protocols is reliable in adults over a wide age range. Ninety-seven healthy adults (age from 21 to 80 years) were randomly assigned to one out of two lean angle protocols: gradual increase to maximal forward-lean angle (maximal lean angle; n  = 43; seven participants were excluded due to marker artefacts) or predefined lean angle (single lean angle; n  = 26; 21 participants needed to be excluded due to multiple stepping after release or marker artefacts). Both protocols were repeated after 0.5 h and 48 h to investigate intra- and inter-session reliability. Stability recovery performance was examined using the margin of stability at release (MoSRL ) and touchdown (MoSTD ) and increase in base of support (BoSTD ). Intraclass correlation coefficients (confidence intervals at 95%) for the maximal lean angle and for the single lean angle were respectively 0.93 (0.89–0.96) and 0.94 (0.89–0.97) in MoSRL, 0.85 (0.77–0.91) and 0.67 (0.48–0.82) in MoSTD and 0.88 (0.81–0.93) and 0.80 (0.66–0.90) in BoSTD, with equivalence being revealed for each parameter between all three measurements ( p  < 0.01). We concluded that the assessment of stability recovery performance parameters in adults over a wide age range with the means of the forward lean-and-release test is reliable, independent of the used lean angle protocol.